THE ANTI-OXIDANT EFFECTS OF GINGER AND CINNAMON ON SPERMATOGENESIS DYS-FUNCTIONING DIABETES RATS. - Khaki, Arash; Khaki, Amir Afshin; Hajhosseini, Laleh; Golzar, Farhad Sadeghpour; Ainehchi, Nava (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Diabetes has being linked to reproductive dysfunction and plant medicine has been shown to be effective in its treatment. Anti-oxidants have distinctive effects on spermatogenesis, sperm biology and oxidative stress, and changes in anti-oxidant capacity are considered to be involved in the pathogenesis of chronic diabetes mellitus. Ginger and cinnamon are strong anti-oxidants and have been shown to reduce oxidative stress in the long-term treatment of streptozotocin (STZ)-induced diabetes in animal models. The present study aims at examining the influence of combined ginger and cinnamon on spermatogenesis in STZ-induced diabetes in male Wistar rats. Materials and Methods: Animals (n = 80) were allocated randomly into eight groups, 10 each: Group 1: Control rats given only 5cc Normal saline (0.9% NaCl) daily;Group2: rats received ginger (100mg/kg/rat) daily; Group 3: rats received cinnamon (75mg/kg) daily; Group 4: rats received ginger and cinnamon, (100mg/kg/rat ginger and 75mg/kg cinnamon) daily; Group 5: Diabetic control rats received only normal saline. Group 6: Diabetic rats received 100mg/kg/day ginger; Group 7: Diabetic rats received 75mg /kg/ day cinnamon; Group 8: Diabetic rats received ginger and cinnamon (100mg/kg/day and 75mg/kg /day). Diabetes was induced with 55 mg/kg, single intra-peritoneal injection of STZ in all groups. At the end of the experiment (56th day), blood samples were taken for determination of testosterone, LH,FSH, total anti-oxidant capacity, and levels of malondialdehyde, SOD, Catalase and GPX. All rats were euthanized, testes were dissected out and spermatozoa were collected from the epididymis for analysis. Results: Sperm numbers, percentages of sperm viability and motility, and total serum testosterone increased in ginger and cinnamon and combined ginger and cinnamon treated diabetic rats compared with control groups. Serum testosterone, LH and FSH were higher compared to control group and also serum anti-oxidants (TAC, SOD, GPX and catalase) all were increased at the end of treatment. Combined ginger and cinnamon showed more intense increase in all parameters compare to ginger and cinnamon alone. Most of the results were significant (P<0.05). Conclusion: We concluded that combined ginger and cinnamon have significant beneficial effects on the sperm viability, motility, and serum total testosterone, LH,FSH and serum anti-oxidants’ level and could be effective for maintaining healthy sperm parameters and male reproductive function in diabetics.